Secretory immunoglobulin a and its role in formation of clinical course of shigellosis in children infected with Helicobacter pylori - Kurlan, N (Annals of Mechnikov’s Institute, 2019)
Introduction. Secretory immunoglobulin A (sIgA) is a crucial factor in protection of the gastrointestinal (GI) tract mucosa directly providing the first line of defense of the intestine from the impact of foreign antigens. At the same time, sIgA is able to form immune complexes not only with infectious agents and their constituent elements, which are found in the mucous membrane, but also with those, which for some reasons overcome the epithelial barrier and directly penetrate lamina propria. The release of sIgA from plasma cells occurs influenced by IL-4, IL-5, IL-6, IL-10 cytokines. Formation of long-term infectious processes as well as chronic pathology associated with increased local immunity, sIgA in particular, is considered in a range of studies. The local immunity factors are of great importance in combination with two or more pathogenic causative agents that can be present in the intestine for a long time. Taking into consideration that Shigellosis mortality rate among children is still high up to now, the issue focused on local immunity state in children with Shigellosis, infected with Helicobacter pylori is currently of concern. Purpose of the study is to explore local immunity competence in children with Shigellosis, infected with Helicobacter pylori by means of sIgA level assessment. Materials and methods.The study involved 68 children aged from 1 to 3,who were diagnosed with Shigellosis Sonnei of medium severity. Additionally, the determination of H. pylori in feces and the level of sIgA in coprofiltrate were provided. Results and discussion. Significantly higher sIgA level, in comparison with the same values of the control group, was revealed in coprofiltrates of all children in acute period. At the same time, in children of Group 2 sIgA content was significantly higher than the values of patients with background infection. The qualitative sIgA content restored and significantly did not differ from the values of the control group in early convalescence period of Shigellosis in children without background infection. However, significant difference was observed with acute period value. sIgA concentration in children infected with H. pylori in the period of clinical recovery was significantly decreased in comparison with acute period values. It was significantly different from the data of healthy children and the children ofGroup 2. The findings obtained are indicative of imbalance of local immunity competence of the intestine in Shigellosis in children infected with H. pylori, especially impaired sIgA production. Insufficient sIgA secretion in coprofiltrates of patients with Shigellosis, that has been revealed, is not contrary to the hypothesis of some scientists concerning the capacity of pathogenic H. pylori strains to carry out their cytotoxic effect associated with decrease of local protective mechanisms of the GI tract mucosa as well as system immunity, the ability to spin out of control of specific immunity mechanisms up to development of immune-dependent inflammation forms. Taking the revealed differences of sIgA content in coprofiltrates in Shigellosis in patients with and without background infection with H. pylori into consideration, we have carried out the study of correlational connection concerned with assessment of Pearson coefficient of this value with basic clinical laboratory values. Present correlational interactions between sIgA values in coprofiltrates of children suffering from Shigellosis, infected with H. pylori, and frequency of development of specific symptoms along with their duration, are indicative of sIgA role in formation of pathogenic mechanisms of the disease course. Conclusion. Therefore, Shigellosis in children infected with H. pylori is accompanied by substantial impairment of local immunity competence that influences the frequency of manifestations of some clinical symptoms and pathologic changes of laboratory values, their duration. The data obtained allow to assume as the perspective direction in perfection of therapy of such patients use of complex immunoglobulin medications should be aimed primarily at inflammatory processes stopping.